2010
DOI: 10.4314/ijest.v1i1.58073
|View full text |Cite
|
Sign up to set email alerts
|

Solving the <i>K-of-N</i> Lifetime Problem by PSO

Abstract: In wireless sensor networks, application nodes (ANs) may be produced by different manufacturers and may own different data transmission rates, initial energies and parameter values. When different kinds of ANs exist in a wireless network, it is hard to find the optimal base-station (BS) locations for minimizing power consumption and prolonging network lifetime. In this paper, a heuristic algorithm based on PSO is thus proposed to solve the K-of-N lifetime problem under general power-consumption constraints in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…From the figure, it is observed that ps=40 is a good choice with a small average error and a reasonable execution time. Similar observation is also reported in [92].…”
Section: Effect Of Pso Parameters On Localization Performancesupporting
confidence: 91%
“…From the figure, it is observed that ps=40 is a good choice with a small average error and a reasonable execution time. Similar observation is also reported in [92].…”
Section: Effect Of Pso Parameters On Localization Performancesupporting
confidence: 91%
“…These micro-sensor nodes characterize by self-configuration and self-adaptation, generally, they are alimented by non-rechargeable batteries. Numerous applications use the WSN by reason of the weak-cost, the self-organization of nodes, the sensing ability of sensors, the miniature dimension of the node which allows it to be deployed in hard environments to supervise different types of physical and environmental conditions, easy in positioning, scattering over an large region and giant fault tolerance [3][4][5]. However, the WSN faces several issue related to the power source.…”
Section: Introductionmentioning
confidence: 99%